Optimizing Social Media and Paid Advertising in Digital Marketing Strategy to Increase Branding and Customer Engagement PT. KB Valbury Sekuritas - Bening, Pijar Elsanti Surya; Roostika, Raden Roro Ratna (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study examines the effectiveness of digital marketing strategies in enhancing branding and customer engagement at PT KB Valbury Sekuritas. Using a qualitative approach with interviews, observation, and documentation, this research analyzes the company's digital marketing strategy implementation through social media platforms, particularly, Instagram and TikTok. The results show that the key indicators of success include engagement rate, conversion rate, and customer feedback. However, several challenges were identified, such as maintaining content relevance, increasing audience engagement, and addressing human and technical resource limitations. To overcome these challenges, the recommended optimization strategies include improving content consistency, using paid advertisements, and decentralizing digital marketing at the branch levels. These findings are expected to help PT KB Valbury Sekuritas develop more effective digital marketing strategies to strengthen brand identity and increase customer loyalty